Revistas Veja e Época : um olhar complexo - Azubel, Larissa Lauffer Reinhardt (2012)
This study will seek to understand and explain the production of meaning in magazine journalism, from a complex view to weekly magazines, Veja and Época. To investigate the spinning of significations, we need the unraveling of the weave. To this end, we selected the categories, a priori, that will guide our gaze: Figures of Language, from Domingos Paschoal Cegalla, and Stereotype, Myth, Culture, Power and sociolect, from Roland Barthes. Through them, barthesian Semiology, as analysis technique, and Paradigm of Complexity morinean, as research method, we will quest for decoding of signs of our object. During the course of investigation, we will see, still, two categories emerge a posteriori, that will contribute to our vision and vidence of speech in magazines: Postmodernity, from Michel Maffesoli, and Self-Help, from Arnaldo Chagas. On this basis, theoretical and methodological, we will reflect by a transdisciplinary and dialogic way on the metamorphoses in making and narrating of the magazines, at contemporaneity. We will see that the interactions, complementary, competing and antagonistic, between reason and emotion, ethics and esthetics, wisdom and dementia, reveals a postmodern magazine journalism, with their own strategies for adherence and enchantment